Pengaruh Pembelajaran Daring terhadap Kepuasan Belajar Mahasiswa Pariwisata di Tarutung - Apriliana Lase; Angelia Putriana; Siti Aisyah; Apriliani Lase (Yayasan Literasi Sains Indonesia, 2023)
Online learning has become an essential part of higher education, particularly during the COVID-19 pandemic. However, its effectiveness in fostering student learning satisfaction needs further investigation, especially in the field of tourism which requires hands-on experience. This study aims to analyze the influence of online learning on the learning satisfaction of tourism students in Tarutung. The research employs a quantitative approach, involving tourism students in Tarutung as the sample. Data was collected through questionnaires that measure various aspects of online learning and learning satisfaction. Multiple linear regression analysis was used to identify the influence of online learning variables on learning satisfaction. The findings indicate that the quality of learning materials, interaction with lecturers, and technology support have a positive impact on student learning satisfaction. Students feel satisfied when the learning materials are relevant, lecturers are responsive, and technology supports the learning process. Conversely, limited social interaction and technical difficulties negatively affect learning satisfaction. Students feel less satisfied when interaction with peers is limited and they encounter technical difficulties in online learning. This study provides valuable insights for universities in Tarutung to enhance the quality of online learning in the field of tourism. Improving the quality of materials, lecturer-student interaction, and technology support can create a more satisfying learning experience. Additionally, it is necessary to seek solutions to increase social interaction and overcome technical difficulties in online learning. Thus, tourism students can achieve optimal learning outcomes even in an online learning environment